Pengembangan Permainan Monopoli untuk Meningkatkan Kognitif, Bahasa dan Sosial Emosional Anak Usia Dini - Mega Putri; Baik Nilawati Astini; I Wayan Karta; I Nyoman Suarta (Indonesian Publication Center, 2021)
Monopoly game is a game developed and played on a game board that has been designed according to the development needs of children aged 5-6 years with a plant theme consisting of two dice, a red card deck, green card, number card, letter card and money as a medium of exchange. The data collection method used is the method of observation, documentation and expert testing. This study applies a descriptive qualitative method with data collection techniques using triangulation. The data were analyzed qualitatively. The subjects of this study were children aged 5-6 years in Gerantung Subdistrict, Praya Tengah Subdistrict, to determine the cognitive, language and social emotional abilities of early childhood using developed monopoly games. The results of game trials on subjects with four children aged 5-6 years resulted in changes in the steps and ways of playing so that they are appropriate for use in children. The result of this research is the development of monopoly game which consists of 17 game steps. Based on the effectiveness test in measuring the cognitive, language and social emotional abilities of children aged 5-6 years, it is found that this monopoly game can improve cognitive abilities with high categories, language skills with categories. moderate and high category of children's emotional social skills. From the results of the game effectiveness test as a group showed that 100% of the subjects experienced an increase in cognitive, language and social emotional abilities.